Feasibility test of STEM at home prototype kit as science project-based learning media for Junior High School students - Zulirfan Zulirfan; Yennita Yennita (Postgraduate, University of Mataram, 2022)
To promote the application of the STEM approach in science learning, it is necessary to provide cheap, easy-to-obtain, and effective STEM project support materials. In addition, science teachers should try to plan and implement STEM in their teaching, even for simple projects. To overcome the problem of the length of time on projects in science teaching, we propose